Use, and perceived usefulness, of cognitive behavioural therapy techniques for self-care among therapists. (2020) - Andersson, Gerhard; Björklind, Andreas; Bennett-Levy, James; Bohman, Benjamin
Abstract: Mental health problems are prevalent among therapists and may have a negative impact on therapist effectiveness. To counteract such problems, therapist self-care (for example, striking a balance between personal and professional demands and seeking personal therapy), has received increased attention. Conceptually, self-care can be considered as part of a personal practice model, focusing on techniques that therapists engage with self-experientially with a focus on their personal and/or professional development. However, studies of the self-application of specific treatment techniques are lacking. We aimed to explore the use, and perceived usefulness, of cognitive behavioural therapy (CBT) techniques for self-care to prevent or treat own mental health problems among practising therapists. Participants were therapists ( n = 228) of various professional backgrounds in Sweden. Data were collected using a web-based survey. Descriptive statistics were calculated, and non-parametric analyses conducted to investigate associations of 13 CBT techniques with therapist characteristics. Use of CBT techniques for self-care was highly prevalent among participants, and they perceived the techniques as useful, irrespective of characteristics such as gender, age, profession, years since graduation, clinical experience, level of training in CBT, and previous experience of personal CBT. The high prevalence among therapists of the use of treatment techniques for self-care is very encouraging. Therapist self-care, including the self-application of treatment techniques, may be an important factor for therapist effectiveness, which calls for further development of personal practice models with respect to self-care, and future studies investigating associations between therapist mental health, self-care, effectiveness and patient outcome. Key learning aims: (1) Therapist self-care using cognitive behavioural therapy (CBT) techniques to prevent or treat own mental health problems may influence therapist effectiveness. However, studies of self-application of treatment techniques are lacking. (2) In the present survey study, the use of CBT techniques for self-care was highly prevalent among practising therapists, and they perceived the techniques as useful, irrespective of characteristics such as gender, age, profession, years since graduation, clinical experience, level of training in CBT, and previous experience of personal CBT. (3) Almost all therapists believed that it was a good idea to self-apply CBT techniques for their own sake and for the benefit of their patients.